TERT Expression in Pituitary Adenomas - Nuray CAN; Mehmet ÇELİK; Buket YILMAZ BÜLBÜL; Necdet SÜT; Filiz ÖZYILMAZ; Semra AYTÜRK; Sibel GÜLDİKEN; Nurtaç SARIKAŞ; Fulya ÖZ PUYAN; Tülin Deniz YALTA; Ali Kemal KUTLU (Federation of Turkish Pathology Societies, 2017)
Objective: Although pituitary adenomas have benign histomorphological features, some of them may present in an aggressive manner. To predict the behaviour of these tumours, telomerase reverse transcriptase (TERT) activity in pituitary adenomas has been the subject of a few studies with contradictory results. This study aims to investigate whether immunohistochemical expression of TERT differs in neoplastic and nonneoplastic pituitary tissues and aims to investigate whether TERT expression is related to clinicopathological features of pituitary adenomas. Material and Method: The study included 48 patients who had been diagnosed with pituitary adenomas and had clinical follow-ups. Nonneoplastic pituitary tissues were obtained from autopsy specimens (n=20). Immunohistochemistry for TERT antibody was performed. Both the nuclear and cytoplasmic expression of TERT antibody was noted, and total combined TERT staining was evaluated according to nuclear and cytoplasmic stainings. Results: TERT expression did not differ between neoplastic and nonneoplastic pituitary tissues. Neither total (combined nuclear and cytoplasmic) TERT nor nuclear TERT expression revealed any statistically significant relationship with any of the clinicopathological features. Higher cytoplasmic TERT expression was observed in adenomas with recurrence than adenomas without recurrence (p=0.035). Conclusion: This study introduces the notion that immunohistochemical expression of TERT does not differ in neoplastic and nonneoplastic pituitary tissues. Pituitary adenomas with cytoplasmic immunohistochemical expression of TERT have significantly higher rates of recurrence. Further studies, including combined methods of immunohistochemistry and molecular analyses in larger groups, may reveal applicable results for the clinical significance of TERT in pituitary adenomas.